Educational Goals from Perspective Hadith - Linda Suanti; Farid Fauzi; Onrico Candra; Rezi Maswar (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2024)
This article tries to reveal the signals of educational goals contained in the hadith of the Prophet SAW. Among them are becoming a devout servant of Allah, a responsible leader becoming a perfect human being, and achieving salvation in this world and the hereafter. This research uses a qualitative method with a thematic analysis approach, namely collecting hadiths that talk about one theme and then discussing them thoroughly, from various aspects. The author attempts to present and explain the aims of education for students so that they have intellectual intelligence, can interact with society, and become people of faith and piety based on the guidance of the hadith of the Prophet SAW.